Pengaruh Inovasi Proses, Inovasi Produk, dan Teknologi Terhadap Kinerja Operasional Pada PT Pagilaran UP Pagilaran Batang, Jawa Tengah - Rahma Ulfa; Dody Setyadi; M. Nahar (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2021)
This study aims to find out the partial and together influence variables of process innovation, product innovation, and technology for operational performance at PT Pagilaran UP Pagilaran. The data analysis technique used multiple regression as technique analysis. The data collection methode in this study used are observation, questionnaires, and documentation. The analytical technique used is multiple regression analysis using SPSS with the results of the equation Y = 1.609 + 0.364X1 + 0.388X2 + 0.274X3. From this analysis it can be concluded that process innovation, product innovation, and technology have a positive effect on operational performance. Based on the results of the coefficient of determination test shows that process innovation, product innovation, and technology affect operational performance by 71.7% while 28, 3% is influenced by other variables that are not explained in this study. The results of the t-test and f-test in this study indicate that process innovation, product innovation, and technology have a significant effect on operational performance either partially or simultaneously.